Squamous cell carcinoma of the tongue in a patient with rothmund-thomson syndrome (Recq4 Mutation) - intolerance to radiotherapy - Hamidah A,; Mazlina M,; Zarina AL,; Muhaizan WM,; Fuad I,; Jamal R, (Penerbit UKM, 2009)
We report a case of squamous cell carcinoma of the base of the tongue in a 27 years old patient with Rothmund-Thomson syndrome (RTS). An abnormal DNA repair mechanism in some RTS patients predispose them to malignancy and influence the tolerance to radiotherapy.